THU0633 The Revised Bristol RA Fatigue Nrs, Containing New Nrs-Coping Anchors (Braf-NRS V2 Revised): Validity across 6 European Countries. (15th July 2016) - Hewlett, S.; Nicklin, J.; Bode, C.; Cramp, F.; Carmona, L.; Davis, B.; Dures, E.; Engelbrecht, M.; Fransen, J.; Gossec, L.; Greenwood, R.; Hagel, S.; et al.
Abstract : Background: BRAF-NRS are a trio of items for fatigue severity, impact and coping. At development, patients wanted the NRS-Severity & Impact anchors to read 0=No fatigue/effect, 10=Totally exhausted/Great deal of effect, but the NRS-Coping to read 0=Not at all well, 10=Very well. 1 Construct and criterion validity of the NRS-Coping-NRS are less strong than NRS-Severity and Impact; 2 cognitive interviewing shows patient confusion over Coping anchors. 3 Objectives: Test construct and criterion validity of BRAF-NRS V2, which has Revised NRS-Coping anchors of 0=Very well, 10=Not at all well (NRS-Severity and Impact unchanged), in 6 EU countries. Methods: RA patients from France, Germany, Netherlands, Spain, Sweden and UK completed the BRAF-NRS V2 Revised, BRAF-NRS Original, BRAF-MDQ, RAID, SF-36. Spearman's correlations assessed criterion and construct validity. Results: Of 1276 patients 76% were female, median HAQ 1.0 (IQR 0.375–1.5). Mean BRAF-NRS-Coping Revised 4.0 (SD 2.66) vs Original 5.95 (SD 2.57), NRS-Severity 4.86 (SD 2.56), NRS-Impact 4.61 (SD 2.69). BRAF-NRS-Severity and Impact had appropriate validity with all 18 variables, overall and by country (r=0.46–0.96). Table shows BRAF-NRS-Coping Revised had better validity than NRS-Coping Original in all variables overall (stronger correlations bolded), and for 15–18/18 variables in all countrie except Spain (3/18). The difference in strength of correlations between the versions was large for the total sample, but minimal for Spain. Conclusions: BRAF-NRS V2 Revised has construct and criterion validity across 6 EU countries. Whilst the BRAF-NRS-Coping Original is acceptable, the BRAF-NRS-Coping Revised has greater validity. In Spain, the validity of both versions is lower but similar to each other. Further exploration of the concept and wording of "coping" in the Spanish population is warranted. References: Nicklin et al 2010a; Nicklin et al 2010b; Hewlett et al 2016 in press Acknowledgement: EULAR project grant EP1009 Disclosure of Interest: None declared